PENGEMBANGAN MEDIA SPINNING WHEEL CARD PORSI GIZI SEIMBANG SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS PADA ANAK - Masriani, Yulia; Herdhianta, Dhimas (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes is metabolic disease that causes the third highest mortality rate in Indonesia. In West Java, prevalence of DM reaches 1.74% of the total population. Bandung Regency is one of the areas that has a high prevalence of DM in West Java at 35.63%. Bandung Regency, Banjaran Sub-district is recorded as a sub-district with prevalence that continues to increase every year. DM disease, especially Type 2 DM, can be prevented by implementing balanced nutritious food consumption early as possible. This behavior can be applied if children have good knowledge. Therefore, a proper information media is needed for children to increase their knowledge related to balanced nutrition as effort to prevent DM. Objective: Develop and analyze effect of Spinning wheel Card media on portion of balanced nutrition as a prevention of diabetes mellitus in children. Methods: This research is Research and Development using 4D (Define, Design, Development, Dissemination). Analysis the effect of the media is at the development stage with a one group pretest posttes design. Results: the define stage, the need for media that can be played and lightweight to carry is obtained. Design media in the form of spinning wheel cards containing balanced nutrition and diabetes prevention material. Development obtained media feasibility results of 75% from material experts, 98% from media experts, and 99% from the target. Conclusion: The spinning wheel card media for balanced nutrition portions is very feasible to use as educational media and can have influence on the knowledge of class 5A SDN Sirnagalih students.